Farrow to finish enterprise budget analysis - Mattos, Zilda Paes de Barros; Duarte, Lafayette Parreira (Pesquisa Agropecuaria Brasileira, 2014)
The main objective of this study was to develop a budget model for farrow to finish swine enterprise, for microcomputer, for Brazilian conditions. To achieve this objective, the electronic spreadsheet Lotus 1-2-3 was used. From animal production indices, expected costs and prices, the model estimates expected profit, feed and cash requirements for a one-year period and also analyses the effect of a change in the number of weaned pigs per litter and in the farrowing interval on the profitability of the enterprise. A real world example is presented at the end of the results and discussion section.
Keywords: budget; planning; swine enterprise